PENGARUH ‘EDAN-EDANAN’ DI DALAM TARI NIRBAYA KARYA SETYASTUTI - Risang Ayu Agustin (Saraswati)
Nirbaya dance is created by Setyastuti, it is a new oriented dance on tradition ‘edan-edanan’ as source her creation. ‘Edan-edanan’ as tradition ritual in temanten agung Kraton ceremony Yogyakarta, which has function as repellent of bala. The configuration of ‘edan-edanan’ describes two crazy people (women an men) who are believed able to expel supranatural things,which can annoy this event. In Nirbaya dance will seem result of influences affecting, it is influence of ‘edan-edanan’ as  creation  isource object in new dance creation. That influence can be seen from ‘edan-edanan’ elements which it can still be identified in nirbaya dance. Visual effect is in make up, costume, property and motion, whereas from point aspect is in tolak bala which is still in Nirbaya dance. Keyword: ‘edan-edanan’, nirbaya, influence